Innovation in Accounting- The Forensic Accounting (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Innovation in every field is an essential requisite. Forensic Accounting  in the field of accounting is also considered to be essential due to the  rapidly increasing number of frauds. Innovation in Accounting in terms  of Forensic Accounting has taken place due to the increased number of  corporate scams in an unmatchable speed. Frauds are spreading like  a communicable disease by victimizing the corporate world in such a  manner that the investors and economy as a whole finds difficult to re cover from it. In India the rate of rapid increase in the number of white  collar crimes and frauds and lack of sufficient expertise to prevent these  practices brings attention towards Forensic Accounting. Scams done by  Ketan Parekh, Harshad Mehta and the Satyam Scam have shaken the  economy and resulted in the increased demand of the Forensic Accoun tants so that preventive actions can be taken before it becomes a curse.  Specialized knowledge in the field is a prerequisite for becoming a foren sic accountant. Some agencies are actively engaged in this field but there  still exists a gap in the demand and supply of the forensic accountants.  This paper makes an attempt to discuss the meaning, innovation and need  of forensic accounting, hub of frauds and the working of forensic accoun tants to control it, prerequisites of a forensic accountant and the present  status of forensic accounting and forensic accountant in India.
Keywords: Forensic Accounting; Frauds; Forensic Accountants; Indiaforensic and Fraud Examiners